Penerapan Distribusi Poisson-Lindley pada Data Jumlah Gol Hasil Pertandingan Liga 1 Indonesia Tahun 2004 - Fakhriel Muhammad Hafizh; Aceng Komarudin Mutaqin (Bandung Conference Series: Statistics, 2022)
Abstract. Liga 1 Indonesia is the highest caste football competition between clubs in Indonesia. First held in 1994, Liga 1 is a merger of the previous 2 major competitions, namely the union (1931-1994) and Galatama 1979-1994). The aim is to improve the quality of Indonesian football and mark the phased league system of Indonesian football at a competitive level. There have been many studies conducted by researchers in various countries to process data on the number of goals scored by football matches for home teams and away teams from a football league. Ghitany and Al-Mutairi (2009) discuss the Poisson-Lindley distribution, a distribution for data from discrete random variable. In this Journal, we will discuss the application of the Poisson-Lindley distribution to the data on the number of goals of home teams and away teams resulting from the highest caste Indonesian football league matches for 2004 and to find out whether the Poisson-Lindley distribution is a suitable distribution of opportunities to model the case of the number of goals data. The maximum likelihood estimation is used to assess the parameters on such distributions. The distribution match test used is the Chi-squared test. As research material, secondary data from recording results will be used obtained from several sources, namely rsssf.com, id.soccerway.com, Wikipedia.com and presented into data on the results of the 2004 Indonesian Liga 1 football match. Based on the results of the application to the data on the number of goals resulting from the Indonesian Liga 1 football match in 2004, the Poisson Lindley distribution is suitable for modeling the case of away team goal number data and is not suitable for modeling the case of home team goal number data. Abstrak. Liga 1 Indonesia adalah kompetisi sepak bola kasta tertinggi antar klub di Indonesia. Terselenggara pertama kali pada tahun 1994, Liga 1 merupakan penggabungan 2 kompetisi besar sebelumnya yaitu perserikatan (1931-1994) dan Galatama 1979-1994). Tujuannya untuk meningkatkan kualitas sepak bola Indonesia dan menandai sistem liga bertahap sepak bola Indonesia di tingkat kompetitif. Sudah banyak penelitian yang dilakukan oleh para peneliti di berbagai negara untuk mengolah data jumlah gol hasil pertandingan sepak bola untuk tim kandang dan tim tandang dari suatu liga sepak bola. Ghitany dan Al-Mutairi (2009) membahas distribusi Poisson-Lindley, suatu distribusi untuk data dari peubah acak diskrit. Dalam Jurnal ini akan dibahas mengenai penerapan distribusi Poisson-Lindley pada data jumlah gol tim kandang dan tim tandang hasil pertandingan Liga sepak bola Indonesia kasta tertinggi untuk tahun 2004 dan untuk mengetahui apakah distribusi Poisson-Lindley merupakan distribusi peluang yang cocok untuk memodelkan kasus data jumlah gol tersebut. Metode penaksir kemungkinan maksimum digunakan untuk menaksir parameter pada distribusi tersebut. Uji kecocokan distribusi yang digunakan adalah uji Chi-kuadrat. Sebagai bahan penelitian akan digunakan data sekunder hasil pencatatan yang diperoleh dari beberapa sumber yaitu rsssf.com, id.soccerway.com, Wikipedia.com dan disajikan menjadi data hasil pertandingan sepakbola Liga 1 Indonesia tahun 2004. Berdasarkan hasil penerapan pada data jumlah gol hasil pertandingan sepakbola Liga 1 Indonesia tahun 2004, distribusi Poisson Lindley cocok untuk memodelkan kasus data jumlah gol tim tandang dan tidak cocok untuk memodelkan kasus data jumlah gol tim kandang.